Algorithm of stretching adjustment of leather with mineral filling - Козарь, Оксана Петрівна; Коновал, Віктор Павлович; Boguslaw, Wozniak; Оленіч, Андрій Васильович (Eastern-European Journal of Enterprise Technologies, 2014)
The ability of the skin to the formation and preservation of form in service depends on its ability to stretch and balance of the elastic and plastic (permanent) deformation. The values of the components of the deformation of the skin with the mineral content in the test mode, one full cycle ”loading - unloading - rest” indicates that the type of mineral filler significantly affects the elastic- plastic properties of the skin. Dependence of residual elongation of tested leather with repeated uniaxial stretching on the degree of hydration of the skin, stretching size and number of repeated stretching have been considered in this paper. Experimentally confirmed hypothesis and mathematical model of stretching adjustment of the leather with multisycle stretching and fixing of material in a stretched state . Patterns of change and the quantitative value of the residual elongation of skin samples with montmorillonite dispersion mineral content have been obtained. The most appropriate treatment process of tricyclic stretching mode and optimum humidification have been proposed. It has been proved that after 2-3 fold prior stretching of the leather the strength is not reduced , but rather strengthens, the value of which depends on the relative size of tensile and relative amount of dampening material before stretching.